Does music quality matter for audience voters in a music contest? - Oliver Budzinski; Marie Kohlschreiber; Björn Kuchinke; Julia Pannicke (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2019)
There are numerous studies analyzing factors of success in media-broadcasted artistic contests, especially music competitions. However, one factor that is generally neglected in the literature is the quality of the artistic performances (i.e. "music quality"). In this paper, we approach this research gap by developing two novel concepts of music quality and by employing unique measures during the empirical analysis of a popular German music television contest in order to analyze how different dimensions of the music and performance quality influences the final voting results. We use the complete historical voting dataset of the music contest from its inception in 2005 until its last broadcast in 2015, collecting 2,816 observations in total. First, we define dimensions of "objective quality" according to insights from musicological research/literature. Second, we conceptualize dimensions of "subjective quality" because music preferences may be subjective and are not necessarily based on how experts' define "good" music. We measure these subjective dimensions in an experimental setting with students from two German universities. Our analysis shows that different quality dimensions affect the outcome of voting results in different ways and not all quality dimensions reveal themselves as significant. In general, subjective quality dimensions turn out to be more relevant than objective ones. The differentiated results of our analysis support the value of our approach to deconstruct quality into different dimensions and test them individually.
Keywords: L82; Z10; C50; 330; music contest; cultural economics; media economics; econometric analysis; success factors; voting bias; music industry